THE NEEDS OF CAREGIVERS OF BIPOLAR PATIENTS - van der Walt, Ilse Annemarie; Carbonatto, Charlene Laurence (Social Work/Maatskaplike Werk, 2019)
Bipolar disorder (BD) is a mental health disorder that affects not only the person living with this chronic disease, but also the family and caregiver. Caregivers, often family members, do not realise how caregiving will impact on them and the rest of the family, until they experience it first-hand. This qualitative study used a collective case study and one-to-one interviews. Non-probability purposive sampling was used with selection criteria. One of the themes generated from the study was the needs of caregivers of patients with BD. Sub-themes included: acknowledgement, sacrificing their own needs, support (emotional and financial), information/knowledge, skills, tools and coping mechanisms, space/freedom/day off, order and stability, need for a programme and future plans. It was found that it is essential to address the needs of caregivers